Fishery of yellowfin tuna Thunnus albacares (Bonnaterre, 1788) in the Indian EEZ with special reference to their biology and population characteristics - Abdussamad, E. M.; Said Koya, K. P.; Rohit, Prathibha; Joshi, K. K.; Ghosh, Shubhadeep; Elayath, M. N. K.; Prakasan, D.; Sebastine, Manju; Beni, M.; Syda Rao, G. (Indian Journal of Fisheries, 2012)
The fishery and population characteristics of yellowfin tuna, Thunnus albacares were monitored during 2006-’10. They were being caught as bycatch along the coasts of Indian mainland and island territories by several coast-based fishery for a long time. Their landings by coast-based fishery was very nominal (4,171 t year-1 average for 1985-2000) with considerable annual fluctuations until targeted fishery for the species developed during the last decade. This resulted in considerable improvement in landings to a peak of 37,963 t in 2007. The production declined thereafter due to shift in the target resource of these vessels from yellowfin tuna to billfishes and elasmobranchs. The annual average catch by Indian flagged â€œletter of permitâ€ (LOP) vessels during 2006-’10 was 85,928 t. The coast-based fishery exploit mainly surface tunas in the outer shelf, adjacent oceanic areas and seamounts. At national level, the pooled catch was supported by 22 - 202 cm fishes with 66.3 cm as annual mean. Relatively large fishes of 40 to 202 cm with 83.4 cm as mean length and dominated by 58-102 cm groups supported the catch in line fishery. The gillnet fishery comprised 22 to 123 cm fishes dominated by 44-82 cm size and other gears landed 26 to 110 cm size fishes dominated by 42 to 80 cm size. Length at capture was 44.8 cm in gillnets, 60.3 cm in hooks and lines and 42.7 cm in other gears. The length at first maturity was 57.6 cm and optimum length for exploitation was 61.1 cm. They spawn round the year with peak during August-January. The mean relative fecundity was 4,36,330 ova per kg body weight and it varied with size of the fish. Study shows that stock of yellowfin tuna in Indian waters remain very healthy with large proportion of spawning stock biomass. Exploitation range of coastal based fishery being very limited and LOP vessels fishing mainly in international waters, large area of Indian EEZ remain unexploited by the country. Overall assessment of fishery scenario indicates possibility of large proportion of yellowfin tunas, especially larger ones remain inaccessible to Indian fishers and hence considerable scope for expanding the fishery.